Atividade de aprendizagem em um curso de Engenharia Elétrica: um estudo baseado na Teoria da Atividade - Viviane Cota Silva (2012)
This research report presents a description of how the learning activity takes place on a course of Electrical Engineering, in the view of the student. The subject chosen for the research was to Electric Circuits I, which has theoretical (classroom) and practical (lab). The objectives were to understand the elements present in the activity of learning, teaching and learning of scientific concepts, as students they see the contribution of each type of school (theoretical and practical) for their learning, and the possible problems that emerge from this activity learning. To analyze the data collected through participant observationand interviews, I used the Activity Theory. This theory belongs to the field of psychology and deals with the development of the human psyche. It is an adequate theory to analyze any human activity. Scholars in the field of education are becoming more activity theory and seeking to establish a correlation between this area and the assumptions of this theory, formulating guidelines for teaching scientific concepts. To investigate the learning of concepts, I have chosen the concept of Superposition Principle. At that point, I wanted to know if students could verbally define it and use it in conducting an exercise. The results allowed me to verify a disability in learning this concept. A more detailed analysis of the results allows me to understand the structure of the activity and realize that the teaching of scientific concepts in this course needs to be revised. The teaching of concepts with verbal definitions, exercises and collection of evidence is insuficient to promote learning in a satisfactory manner. Ideally the students broke the limits of empirical thinking and learn to think theoretically. This would be possible when the student is involved in a learning activity, the structure of which lead to the internalization of scientific knowledge accumulated historically and culturally, transforming them into cognitive instruments for use in solving problems.